Spiders associated with the flowering of Drimys granadensis (Winteraceae) - MARQUÍNEZ, XAVIER; CEPEDA, JULIANA; LARA, KATHERINE; SARMIENTO, RODRIGO (Revista Colombiana de Entomología, 2010)
Drimys granadensis (Winteraceae) is a common tree in the high-Andean forests, with a system of open pollination by insects. In this work we identified the spiders associated with D. granadensis in relation to the floral phenological phases and the visiting insects. We found a total of 53 mature spiders from seven families (Araneidae, Thetragnathidae, Theridiidae, Linyphiidae, Thomisidae, Salticidae and Aniphaenidae) and 12 morphospecies. The spiders had a preference for flowers in the female and hermaphrodite phases where the dipterans were more abundant. We found a species of Thwaitesia (Theridiidae) foraging exudates of the stigmata. This species has an abdomen with coloration similar to the anthers and a transparent body that helps them be imperceptible in the flowers. The camouflage is also used to hunt by a species of Misumena (Thomisidae), which is similar in color and form to a D. granadensis flower bud.